Analisis Strategi Pemasaran dalam Meningkatkan Volume Penjualan PADA PT. Unilever Indonesia, Tbk - Afriantoni Afriantoni (CITRA EKONOMI, 2020)
The objectives of this study are: 1). To find out the development of sales volume at PT. Unilever Indonesia, Tbk, 2). To analyze the implementation of marketing strategies in increasing sales volume at PT. Unilever Indonesia. The research method used is qualitative research. Data obtained by conducting library research. Data analysis used is data reduction, data presentation and data verification (drawing conclusions).The results of this study are the marketing strategies implemented by PT. Unilever Indonesia, Tbk in increasing sales volume consists of product strategies, pricing strategies, distribution strategies and promotion strategies. The development of unilever home and personal care product sales experienced the highest increase in 2016 which increased by 9.05 percent, then the lowest increase occurred in 2018 which only increased by 0.7 percent and the average sales of home and personal care products for 5 ( five) years, an increase of 3.95 percent. Unilever foods and refreshment products experienced the highest increase in 2015 which increased by 11.8 percent, then the lowest increase occurred in 2017 which increased by 2.8 percent and the average sales of food and refreshment products for 5 (five) years namely increased by 7.28 percent. The results of the analysis of this study are PT. Unilever Indonesia, Tbk applies 4 (four) marketing strategies, which include: 1). The product strategy consists of a strategy of product diversification and product differentiation, 2). The pricing strategy consists of a strategy of low price leadership and price discrimination, 3). Distribution strategy where the flow starts from manufacturers, agents, wholesalers, retailers, and consumers, 4). The promotion strategy consists of advertising, sales promotion, personal selling, direct marketing and public relations with the website.